(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This research paper will investigate the impact of social media on student academic performance. It will explore how social media use can be both beneficial and detrimental to students' grades and study habits. The paper will also discuss potential solutions for mitigating the negative effects of social media on student learning.